Marching Band as a Representation of Santri Da'wah Media at TPQ Al Wasiyah Campurdarat Tulungagung - Rifdah, Nur; Clara Sinta Pratiwi (al-Afkar, Journal For Islamic Studies, 2025)
This research has the aim of: 1) Knowing the use of the Marching Band as a representation of the student da'wah media at TPQ Al Wasiyah Campurdarat Tulungagung. 2) Know the impact of using the Marching Band as a representation of students' da'wah media at TPQ Al Wasiyah Campurdarat Tulungagung. The method in this research is to use a case study approach, with a qualitative type of method. The data source in this research is primary data originating from field data from the TPQ Al Wasiyah environment in Campurdarat District, Tulungagung, East Java, such as teachers, administrators and students. Data collection techniques using documentation, interviews and observation. Finally, the data analysis technique is guided by Miles and Hubberman, namely through data reduction, followed by presenting the data and ending with drawing conclusions. The results of this research show that: 1) The use of the Marching Band as a representation of da'wah media at TPQ Al Wasiyah Campurdarat, Tulungagung, has proven effective for students in strengthening understanding of Islamic teachings. Through a creative and fun approach, this activity is not only a means of entertainment, but also a learning method that suits the characteristics of active students. 2) The impact of use is that apart from increasing enthusiasm for learning, Marching Bands also contribute to the formation of student character, especially in aspects of discipline, responsibility and teamwork. Routine and structured training trains students to respect time, obey rules, and work in one team.